Mengembangkan Kemampuan Berbahasa Anak Melalui Media Gambar Seri Pada Anak Kelompok A Di TK Pertiwi I Blimbing Kecamatan Sambirejo Kabupaten Sragen Tahun Ajaran 2014/2015 - MUSLIMAH, Khoiriah; , Dr. Darsinah, M. Si (2015)
Language ability is an ability that can be developed and stimulated early on. Language skills developed because children are very important in the life of a child is a means to communicate, but the fact that occurs in kindergarten A Pertiiwi I Blimbing, District Sambirejo, Sragen children are still many passive. This research aims to develop the language skills of children through the medium of drawing the series. This research is a classroom action research (PTK). This study was conducted in two cycles, each cycle consisting of two meetings. The subjects were children in group A by using the media image series in TK Pertiwi I, Blimbing, Sragen academic year 2014/2015, amounting to 12 children. The development of language skills of children Data collected through observation. Analytical techniques used include a comparative analysis techniques, interactive analysis, and one-way ANOVA. Based on the results obtained by the percentage of children who reach the achievement of appropriate developmental expectations (BSH) and above that is the prasiklus 33.33%, 83.33% first cycle and the second cycle of 91.66%. In addition, based on the results of the F test with a significance level of 0.05 was obtained F_hitung results greater than 41.776 F_tabel or ≥ 3.28, then Ho is rejected and Ha accepted means there is a significant difference between the results of the development of language skills of children in pre-cycle, cycle The first and second cycle. The conclusion of this study is that the language skills of children in group A in TK Pertiwi I Blimbing, District Sragen Sambirejo academic year 2014/2015 can be developed through the medium of picture series Keywords: Media Picture Series, Proficiency